Parallel features of the activities of mathematics professors in Gdansk, Vilnius and Kenigsberg in the middle of the XVIIth century - Gečiauskas, Evaldas (Lietuvos matematikos rinkinys, 2003)
In the middle of the XVIIth century professors of mathematics in Gdansk, Vilnius and Kenigsberg lectured on arithmetic, geometry, astronomy, calendar and determination of geographical coordinates. Professor Peter Krager of the Gdansk Academic gymnasium also lectured on trigonometry and logarithms. He published scientific works and calendars. Professor Oswald Kffiger of Vilnius university additionally delivered lectures on optics, mechanics and fortification. He published various matheseos investigations. Professors of mathematics of Kenigsberg university Johann Strauss lectured on architectonics, Albrecht Linemann introduced trigonometric triangulation, Andreas Concius arranged disputes on mathematics and astronomy, issued calendars. Professors of mathematics of Kenisberg university were also interested in astrology.